Surface-Emitting Micro-Mirror Superluminescent Diodes: Investigation of Tilt Accuracy Via Far-Field Analysis - Jentzsch, Bruno; Gomez-Iglesias, Alvaro; Tonkikh, Alexander; Zull, Heribert; Kugler, Siegmar; Witzigmann, Bernd (physica status solidi (b), 2019)
Far-field characteristics of novel surface-emitting micro-mirror superluminescent diodes are investigated. The mirrors are fabricated by using thin film technology and an inductively coupled plasma etching process on wafer scale, suitable for mass production. Combining measurements and modeling results, the mirror tilt is estimated and the feasibility of good-quality ≈45° mirrors is demonstrated. This approach offers an accuracy better than optical inspection with, e.g., scanning electron microscopy. In addition, our experiments revealed spurious ripples in the far-field profiles with increasing tilt deviations, which finite-difference time-domain simulations identified as interference with back reflections. These results highlight the importance of tailored waveguides, high quality coatings, and precise mirror tilt to achieve maximal performance with surface-emitting in-plane semiconductor devices.
CRIS-Team Scopus Importer:2021-06-11
Keywords: dry etched mirror; far field; superluminescent diode; surface emission; thin film technology